Life strategies of pacific salmon. Communication 1. Diversity of life forms - S. L. Marchenko (Известия ТИНРО, 2023)
Diversity of life strategies of pacific salmon (gen. Oncorhynchus) is reviewed on the basis of published data. Cases of polycyclicity and changes in life strategy during the ontogenesis are described.